ACE inhibitors versus angiotensin receptor-neprilysin inhibitors for HFrEF management: A prospective cohort study from Indonesia - Heriansyah, Teuku; Lestari, Nova D.; Hadi, Tjut F.; Novia, Rizki; Munawarah, Iffah; Taufiqurrahman, Taufiqurrahman; Yuvhendmindo, Shahcoga L.; Bashori, Ahmad A. (Narra Sains Indonesia, 2024)
Previous studies have reported that angiotensin receptor-neprilysin inhibitors (ARNI) are superior to angiotensin-converting enzyme inhibitors (ACEI) in treating heart failure with reduced ejection fraction (HFrEF). Unfortunately, previously published studies predominantly focused on Western populations, while the data remains insufficient in developing countries. The aim of this study was to compare the efficacies of ARNI and ACEI on patients with HFrEF in Indonesia. A prospective cohort study was conducted among heart failure patients at Dr. Zainoel Abidin Hospital, Banda Aceh, Indonesia. Both ACEI and ARNI each consisted of 40 subjects receiving standard treatment for heart failure. Left ventricular ejection fraction (LVEF), quality of life (QoL), suppression of tumorigenicity 2 (ST2), and troponin T were measured upon admission and at the end of the follow-up. In addition, the occurrence of major adverse cardiac events (MACE) was observed during 6 months of follow-up. Paired t-test was used to compare the outcomes of ACEI and ARNI. The results revealed that KKCQ score and LVEF were improved in both ARNI and ACEI groups (each with p<0.001). A higher KCCQ overall score was observed in the ARNI group in contrast to the ACEI group (p=0.01). ARNI demonstrated superior results in improving the ejection fraction as compared with ACEI (p=0.001). Troponin T and ST2 levels exhibited no significant difference between the two groups (p=0.07 and 0.286, respectively). MACE-associated mortality (p=0.696) and rehospitalization (p=0.955) were identical between both groups. In conclusion, ARNI was more efficacious than ACEI in improving the quality of life and left ventricular ejection fraction of patients with HFrEF. However, the efficacy was not significantly different in reducing the risk of MACE.